COMPREHENSIVE REVIEW OF THE APPLICATION OF HYBRID NANOFLUIDS (HNF) IN MINIMUM QUANTITY LUBRICATION (MQL) FOR SUSTAINABLE MACHINING - Nana Supriyana; Afif Faishal; Dhimas Cahyo Anindito; Kuncoro Diharjo (Jurnal Pendidikan Teknik Mesin, 2025)
Conventional cutting fluids in machining cause environmental and economic concerns. Minimum Quantity Lubrication (MQL) offers a sustainable alternative but faces cooling and lubrication limitations. Integrating hybrid nanofluids (HNF) into MQL significantly enhances machining performance. This review systematically analyzes HNF-MQL applications in continuous machining, examining improved cooling-lubrication mechanisms, performance outcomes, and sustainability. Results indicate HNF consistently outperforms single nanofluids, reducing cutting force, tool wear, and improving surface quality across various hard-to-machine materials. HNF-MQL also lowers fluid consumption, energy use, and environmental impact. However, challenges like nanoparticle stability, cost, and production scalability hinder widespread adoption. HNF-MQL presents an effective green machining strategy, with future research needed in material optimization, advanced delivery systems, and deeper mechanistic understanding.